Implementation of Financial Management of Village-Owned Enterprises According to the Perspective of Fiqh Muamalah: A Case Study in Karangdoro Village - Azizah, Maulida Nur; Munawir, Munawir (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this research is to understand how the application of the fiqh muamalah perspective is implemented in the management of the Village-Owned Enterprises (BUMDes) Mitra Usaha in Karangdoro Village, Tegalsari District, Banyuwangi Regency, East Java. The method used is a qualitative descriptive approach, with data sources including observation, interviews, and documentation. The results of the study indicate that financial management is considered to be good. BUMDes with good performance will have high competitiveness, and achieving this requires quality human resources. This is realized through three businesses operating in the trade sector, namely an agricultural kiosk, a convenience store, and office supplies. Among these, the agricultural kiosk has shown significant progress and has generated a considerable profit. The presence of BUMDes serves as an alternative financing option for the village community to implement interest-free debt financing.